1997
DOI: 10.1266/ggs.72.219
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and characterization of a mariner-like element in the silkworm, Bombyx mori.

Abstract: We have identified a mariner-like element (MLE) in the genome of the silkworm, Bombyx mori. The cloned MLE, desiqnated as BmMLE, contained an ORF that was interrupted by insertions, stop codons, and frameshifts. The complete ORF sequence was estimated by sequencing the PCR products. The hypothetical protein coded by this ORF showed 34% homology to the Mos1 element of Drosophila mauritiana, and is phylogenetically very close to MLE of Hyalophora cecropia. BmMLE is present in 80 to 100 copies in the B. mori geno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
2
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 24 publications
5
22
2
2
Order By: Relevance
“…Although Tomita et al (1997) reported higher levels of genetic variation in Chinese strain classes (compared to the others) by examining the abundance of mariner-like elements mediated by PCR-amplification, our approach did not result in clear differences among the four classes. This discrepancy likely arose from the relatively small number of variable sites in the present study.…”
Section: Segregation Sites In the Coi Coding Regionmentioning
confidence: 63%
See 2 more Smart Citations
“…Although Tomita et al (1997) reported higher levels of genetic variation in Chinese strain classes (compared to the others) by examining the abundance of mariner-like elements mediated by PCR-amplification, our approach did not result in clear differences among the four classes. This discrepancy likely arose from the relatively small number of variable sites in the present study.…”
Section: Segregation Sites In the Coi Coding Regionmentioning
confidence: 63%
“…The DNA samples used in this study were similar to those in Tomita et al (1997), except we excluded the tropical strains because of the small number of strains kept in NIAS. We analyzed 48 Japanese, 50 Chinese, 28 European, and 21 moltinism strains.…”
Section: Genomic Dna Samples Of Native Silkworm Strainsmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-LTR retrotransposons BMC1 (L1Bm) (Ogura et al, 1994;Ichimura et al, 1997;Abe et al, 1998b), the mariner-like DNA-type transposon (Robertson and Asplund, 1996;Tomita et al, 1997;Robertson and Walden, 2003), and the retroposon Bm1 (Adams et al, 1986) are dispersed in this 320-kb region on the Z chromosome. However, the most striking difference compared to the W chromosome is that LTR retrotransposons are not found in this 320-kb region.…”
Section: The Retrotransposable Elements Of the W-specific Bac Clonesmentioning
confidence: 99%
“…These DNA samples were originally used in Tomita et al (1997). We analyzed 48 Japanese, 49 Chinese, 28 European, and 21 molting strains.…”
Section: Methodsmentioning
confidence: 99%